Análise do processo de apropriação dos gêneros discursivos em práticas letradas socialmente valorizadas: redações de alunos do cursinho pré-vestibular da UFSCar - Modro, Marcos Vinícius (2009)
This work investigates the process of appropriation of secondary discourse genres (Bakhtin, 1992) in institutional contexts as a part of processes of social participation. Our main objective was to describe and to understand how students of the Vestibular preparatory Course (Cidade Aracy II neighborhood, in São Carlos) appropriate themselves of discursive and textual mechanisms that imply the meaning manners in the argumentative discourse genres, and as these mechanisms interconnect with the social and discursive structures, as ways of participation in the institutional literacy practices. We consider three theoretical assumptions: discourse genres studies into process of teaching/ learning of Portuguese language; the three-dimensional concept of the language of the English linguist Norman Fairclough (2001); and, the Literacy Studies. The work focuses on the access and students participation in different literacy practices and on the textual elements that they integrate into the textual production of those social contexts. The data collected through semi-structured questionnaire and the textual production of the subject of research demonstrate that the students are involved in an initial process of appropriation of the genres of the institutional sphere. We are referring to the knowledge of certain social rules and specific linguistic and discursive of the social sphere (i.e. the Vestibular exam, the University). The results of this research point to the fact that the teacher, as literacy agent, needs to focus on social activities to provide an enlargement of the students previous knowledge, besides creating opportunities so the students to participate in social reading and writing practices of the different social spheres. Thus, through the qualitative research, we intend to offer subsidies for: a) a responsive reflection concerning the school practices and the processes that involve the production of argumentative texts for the Vestibular exam; b) the understanding in the dialectic relationship among social and linguistic elements in the teaching and learning process of Portuguese language; c) the understanding of the inherent subject to the social mobility, to the social identity construction and to the practices of sense production in the speech and in the writing concerning specific social contexts.